Genome-wide association analysis identifies resistance loci for bacterial blight in a diverse collection of indica rice germplasm - Zhang, Fan; Wu, Zhi-Chao; Wang, Ming-Ming; Zhang, Fan; Dingkuhn, Michael; Xu, Jian-Long; Zhou, Yong-Li; Li, Zhi-Kang (Public Library of Science, 2017)
Bacterial blight, which is caused by Xanthomonas oryzae pv. oryzae (Xoo), is one of the most devastating rice diseases worldwide. The development and use of disease-resistant cultivars have been the most effective strategy to control bacterial blight. Identifying the genes mediating bacterial blight resistance is a prerequisite for breeding cultivars with broad-spectrum and durable resistance. We herein describe a genome-wide association study involving 172 diverseOryza sativa ssp. indica accessions to identify loci influencing the resistance to representative strains of six Xoo races. Twelve resistance loci containing 121 significantly associated signals were identified using 317,894 single nucleotide polymorphisms, which explained 13.3–59.9% of the variability in lesion length caused by Xoo races P1, P6, and P9a. Two hotspot regions (L11 and L12) were located within or nearby two cloned R genes (xa25 and Xa26) and one fine-mapped R gene (Xa4). Our results confirmed the relatively high resolution of genome-wide association studies. Moreover, we detected novel significant associations on chromosomes 2, 3, and 6–10. Haplotype analyses of xa25, the Xa26 paralog (MRKc; LOC_Os11g47290), and aXa4 candidate gene (LOC_11g46870) revealed differences in bacterial blight resistance amongindica subgroups. These differences were responsible for the observed variations in lesion lengths resulting from infections by Xoo races P1 and P9a. Our findings may be relevant for future studies involving bacterial blight resistance gene cloning, and provide insights into the genetic basis for bacterial blight resistance in indica rice, which may be useful for knowledge-based crop improvement